A Study on the Factors affecting the Knowledge of Impact Investing - Selvan, Christo; Pradeep P; SP, Chaithra (International Journal of Psychosocial Rehabilitation, 2020)
Savings and Investment is the key to any nation’s economy growth. It is an integral part of peoples’ daily decision. Impact investors do investment with an intention to impact positively by measuring the impact of social and environmental causes alongside a financial return. These investors tend to invest in different movable and immovable assets like shares, bonds, real estate, mutual funds. This research is to identify the factors influence the investments which made into different sources Questionnaire method applied to identify the awareness of such traditional investors, socially responsible investors and the sources of influences. Samples collected to identify whether education and experience of investors affect the impact investments pattern are key aspects of the study. Risk and return factor after comparison of both SRIs and Traditional investors seems to be identical in a few cases although the motive is different. It is identified that there is a minimal difference between traditional investors and socially responsible investors which adds to our findings and research problem. Through our discussions, we had identified that investors aimed to incorporate both the financial and social objectives in the investment decision. Socially responsible investing has been developed since the 1970s. Today it serves as a vital aspect of investing culture. SRI is a way to promote practices that aid in developing and also concerns about the environment, which separates them from traditional investors. The main focus of this research study is to identify the differences and similarities claimed between SRIs and traditional investors and reveal their earning capacities and the duration required henceforth.